Aging and loss : mourning and maturity in contemporary Japan - Danely, Jason (Rutgers University Press, 2014)
By 2030, over 30% of the Japanese population will be 65 or older, foreshadowing the demographic changes occurring elsewhere in Asia and around the world. What can we learn from a study of the aging population of Japan and how can these findings inform a path forward for the elderly, their families, and for policy makers? Based on nearly a decade of research, Aging and Loss examines how the landscape of aging is felt, understood, and embodied by older adults themselves. In detailed portraits, anthropologist Jason Danely delves into the everyday lives of older Japanese adults as they construct.
Keywords: Aging -- Japan.; Older people -- Japan.; Death -- Social aspects.; Mourning customs -- Japan.; Vieillissement -- Japon.; Personnes âgées -- Japon.; Mort -- Aspect social.; Deuil -- Coutumes -- Japon.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Aging; Death -- Social aspects; Mourning customs; Older people; Japan